Outcomes of transcatheter aortic valve implantations in high-volume or low-volume centres in Germany. Issue 20 (18th February 2020) - Oettinger, Vera; Kaier, Klaus; Heidt, Timo; Hortmann, Markus; Wolf, Dennis; Zirlik, Andreas; Zehender, Manfred; Bode, Christoph; von zur Mühlen, Constantin; Stachon, Peter
Abstract : Objective: Transcatheter aortic valve implantation (TAVI) is the most common aortic valve replacement in Germany. Since 2015, to ensure high-quality procedures, hospitals in Germany and other countries that meet the minimum requirement of 50 interventions per centre are being certified to perform TAVI. This study analyses the impact of these requirements on case number and in-hospital outcomes. Methods: All isolated TAVI procedures and in-hospital outcomes between 2008 and 2016 were identified by International Classification of Diseases (ICD) and the German Operation and Procedure Classification codes. Results: 73 467 isolated transfemoral and transapical TAVI procedures were performed in Germany between 2008 and 2016. During this period, the number of TAVI procedures per year rose steeply, whereas the overall rates of hospital mortality and complications declined. In 2008, the majority of procedures were performed in hospitals with fewer than 50 cases per year (54.63%). Until 2014, the share of patients treated in low-volume centres constantly decreased to 5.35%. After the revision of recommendations, it further declined to 1.99%. In the 2 years after the introduction of the minimum requirements on case numbers, patients were at decreased risk for in-hospital mortality when treated in a high-volume centre (risk-adjusted OR 0.62, p=0.012). The risk for other in-hospital outcomes (stroke, permanent pacemaker implantation and bleeding events) did not differ after risk adjustment (p=0.346, p=0.142 and p=0.633). Conclusion: A minimum volume of 50 procedures per centre and year appears suitable to allow for sufficient routine and thus better in-hospital outcomes, while ensuring nationwide coverage of TAVI procedures.